Family Nursing Care In Hypertension Disease With Nursing Problems Knowledge Deficit With Hypertension Health Education Actions - Ria Ika Imelda; Al-Bahra (JIKO (Jurnal Ilmiah Keperawatan Orthopedi), 2021)
The purpose of this study was to determine Family Nursing Care for Hypertension with Knowledge Deficit Nursing Problems with Hypertension Health Education Actions. The research design is descriptive which aims to describe important events that occur in the present. The type of descriptive research design used is a case study research design. The case study subjects consisted of 2 (two) patients. The focus in the case study is to find out family nursing care in hypertension with the problem of lack of knowledge with health education actions about hypertension. The appropriate ones are: knowledge deficit related to the inability of the family to recognize sick family members. At the intervention stage, the author prepares a nursing care plan for Mr. S and Mr. A, which is to provide health education about hypertension. When this health education was given, respondents followed the directions given to make traditional treatment from star fruit to lower blood pressure. To determine the level of success of nursing actions that provide Health Education. Mrs. S got results before giving Health Education, Ny.S blood pressure was 145/80mmHg and after Health Education, blood pressure was 140/80mmHg. While Mrs. A got the results before explaining Health Education, Mr. A's blood pressure was 140/80mmHg and health education was carried out with the results of blood pressure 135/80mmHg.